2011
DOI: 10.1186/1748-717x-6-162
|View full text |Cite
|
Sign up to set email alerts
|

Induction chemotherapy with paclitaxel and cisplatin to concurrent radiotherapy and weekly paclitaxel in the treatment of loco-regionally advanced, stage IV (M0), head and neck squamous cell carcinoma. Mature results of a prospective study

Abstract: Backgroundto evaluate activity and toxicity of a sequential treatment in advanced, non metastatic, mostly unresectable, head and neck squamous cell carcinoma.MethodsPatients with loco-regionally advanced or unresectable, head and neck cancer, were prospectively treated with 3 courses of induction chemotherapy followed by concurrent chemoradiation. Induction chemotherapy consisted of paclitaxel 175 mg/m2 day 1 and cisplatin 75 mg/m2 day 2, given every 3 weeks, to a total of three courses. Curative radiotherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
4
1
1
Order By: Relevance
“…Multiple single arm studies have shown a promising response rate of 60% to 80% with the 2-drug taxane and platinum regimen. [21][22][23][24] Even these response rates seem higher than the response rate seen in our study. This may be due to a predominant proportion of patients having laryngeal or oropharyngeal primary tumors in these studies compared to our study.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Multiple single arm studies have shown a promising response rate of 60% to 80% with the 2-drug taxane and platinum regimen. [21][22][23][24] Even these response rates seem higher than the response rate seen in our study. This may be due to a predominant proportion of patients having laryngeal or oropharyngeal primary tumors in these studies compared to our study.…”
Section: Discussioncontrasting
confidence: 89%
“…However, whether the TPF regimen is associated with a better response rate than the 2‐drug regimen of taxane and platinum is unknown. Multiple single arm studies have shown a promising response rate of 60% to 80% with the 2‐drug taxane and platinum regimen . Even these response rates seem higher than the response rate seen in our study.…”
Section: Discussionmentioning
confidence: 99%
“…As to be expected, several of these drugs exhibited synergistic effects when being combined with exposure to ionizing radiation (Griem and Malkinson 1966 ; Brues et al 1940 ; Tishler et al 1992 ; Milas et al 1994 , 1996 ; Milross et al 1997 ). This is why some of them (e.g., taxol) not only are adopted in radiochemotherapy but even still are in the focus of current clinical research (Pergolizzi et al 2011 ; Combs et al 2012 ). However, these drugs not only lack the level of specificity current therapies demand for, but they also exhibit side effects, which, in worst case, even limit the therapeutic effort.…”
Section: Biological Improvements Of Radiotherapymentioning
confidence: 99%
“…Triple metronomic chemotherapy (methotrexate, celecoxib and erlotinib) was selected as the MCT schedule based on favourable response rate in platinum-refractory/early failure oral cancers [ 10 ]. Paclitaxel and carboplatin were selected as MTD schedules based on the efficacy and favourable safety profile of this combination [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%